ظواهر القياس النحوي في كتاب سيبويه - Ruchamain, Tsaniya (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
Abstarct Learning Arabic, especially syntax requires deep learning of analogy, and this learning is at the highest level so it is impossible to leave this discussion, but it must be deepened. One of the Nahwu scholars who used analogy in determining law was Sibawaih, the imam of the Nahwu experts. The book by Sibawaih which is duubed the “Qur’an Ilmu Nahwu” is a a source of learning for nahwu because it contains a discussion of Nahwu’s problem, along with its rules, analogy, and their causes. The purpose of this study is to determine the form of analogy in Sibawaih’s book and kinds of kinds. In this discussion, the researcher describe the “Forms of analogy in the Sibawaih’s Book” with the research method of literature research to describe the form of analogy in the Sibawaih’s book, as for the completion of the discussion by examining previous book that discuss the theory. The conclusion of this study is that Sibawaih has used analogy in law-talking in Nahwu science, and these analogy can be seen in his book “Al-Kitab” which is the main source of Nahwu learning from ancient times and today. And this analogy produces nahwu’s laws such as “wujub, man’u, jawaz”. Among the kinds of analogy found in the Sibawaih’s book, namely “qiyas al-‘ilah, qiyas as-syibh, al qiyas allafdhi, al qiyas al ma’nawi” seen from a different point of view.